2013
DOI: 10.3390/molecules181215474
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Activity of Collagen Peptide via ERK/MAPK Pathway Mediated Boosting of Collagen Synthesis and Its Therapeutic Efficacy in Osteoporotic Bone by Back-Scattered Electron Imaging and Microarchitecture Analysis

Abstract: Collagen hydrolysate (CH) has been reported to exhibit a positive effect on bone. In the present study, the in vitro effects of CH (<3 kDa) were examined and the in vivo experiments confirmed the positive effects of CH in ovariectomized (OVX) rats. Bone mineral density (BMD) was examined by DXA analysis. Scanning electron microscopic analysis and quantitative 3D-color backscattered electrons imaging analysis were performed on the lumbar vertebrae. CH increased osteoblastic cell proliferation and alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 28 publications
8
46
2
1
Order By: Relevance
“…These results indicate that Pro-Hyp can promote the differentiation of osteoblasts by upregulating gene expression of Runx2 and Osterix. Previous reports have shown that treatment with crude CP increases the expression of the Runx2 and the Col1a1 genes in osteoblastic cells [13,14]. The regulation by Pro-Hyp in MC3T3-E1 cells would explain a mechanism of the protective effect of CP in bone metabolism.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results indicate that Pro-Hyp can promote the differentiation of osteoblasts by upregulating gene expression of Runx2 and Osterix. Previous reports have shown that treatment with crude CP increases the expression of the Runx2 and the Col1a1 genes in osteoblastic cells [13,14]. The regulation by Pro-Hyp in MC3T3-E1 cells would explain a mechanism of the protective effect of CP in bone metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports have shown that crude CP stimulates the proliferation of osteoblast cells. In one previous report, crude CP was used that may include various collagen-derived di-, tri-, and oligo-peptides such as Pro-Hyp, Pro-Hyp-Gly, Hyp-Gly, or Ala-Hyp [12][13][14]. It is speculated that these collagen-derived peptides, except Pro-Hyp, have the ability to enhance osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Collagens are peptide mixtures with different molecular weights. Hydrolyzed pigskin collagens smaller than 3,000Da are reported to prevent the bone loss due to ovariectomization, and improve microstructure of lumbar bones [18]. Oral medications of collagens smaller than 5,000Da can significantly increase the bone density and strength of ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kim et al 28 considered bone loss to be a non-uniform process because the cancellous bone, the main component of the vertebrae, represents a higher risk than the cortical bone, the main component of the femur. Therefore, the lumbar vertebrae play a key role in monitoring OP.…”
mentioning
confidence: 99%